Advocating for Disability Voting Rights in Framework Ius Constituendum - Taupiqqurrahman, Taupiqqurrahman (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Protecting and guaranteeing the rights of every citizen is the obligation of the state, but in fact there are still acts of discrimination in the rights of citizens experienced by persons with disabilities. One form of discrimination carried out is related to political rights by setting physical health requirements for prospective members of the DPR, provincial DPRD, and district/city DPRD. Although there is no definite limit to measure the level of physical health. In addition, the electoral law contradicts the law on persons with disabilities which states that persons with disabilities have political rights. The electoral law should provide an open space as a means for people with disabilities to become part of public office.  However, this will not be realized without a special quota for persons with disabilities to run as candidates for legislative members, as is the case with the quota of 30% female representation as prospective candidates for the DPR / DPRD and the determination of persons with disabilities as workers in government agencies at least 2% and 1% for private companies. Therefore, regulations should be added related to special quotas for persons with disabilities to become candidates for representation from political parties as election participants